Nanostructured cellulose-xyloglucan blends via ionic liquid/water processing. (15th July 2017) - Bendaoud, Amine; Kehrbusch, Rene; Baranov, Anton; Duchemin, Benoît; Maigret, Jean Eudes; Falourd, Xavier; Staiger, Mark P.; Cathala, Bernard; Lourdin, Denis; Leroy, Eric
Highlights: Bioinspired cellulose-xyloglucan biopolymer blends were synthesized. Films were obtained by regenerated from solutions in an ionic liquid. Water-soluble xyloglucan persisted in the films following regeneration in water. Synergistic mechanical performance, accompanied by nanostructuration, is observed for a cellulose:xyloglucan mass ratio of approximately 1. Abstract: In this work, the properties of cellulose (CE)/xyloglucan (XG) biopolymer blends are investigated, taking inspiration from the outstanding mechanical properties of plant cell walls. CE and XG were first co-solubilized in an ionic liquid, 1-ethyl-3-methylimidazolium acetate, in order to blend these biopolymers with a varying CE:XG ratio. The biopolymers were then regenerated together using water to produce solid blends in the form of films. Water-soluble XG persisted in the films following regeneration in water, indicating an attractive interaction between the CE and XG. The final CE:XG ratio of the blends was close to the initial value in solutions, further suggesting that intimate mixing takes place between CE and XG. The resulting CE/XG films were found to be free of ionic liquid, transparent and with no evidence of phase separation at the micron scale. The mechanical properties of the blend with a CE:XG ratio close to one revealed a synergistic effect for which a maximum in the elongation and stress at break was observed in combination with a high elastic modulus. Atomic force microscopy indicates a co-continuous nanostructure for this composition. It is proposed that the non-monotonous variation of the mechanical performance of the films with XG content is due to this observed nanostructuration.